CD161 expression characterizes a subpopulation of human regulatory T cells that produces IL‐17 in a STAT3‐dependent manner. Issue 8 (3rd July 2013) - Afzali, Behdad; Mitchell, Peter J.; Edozie, Francis C.; Povoleri, Giovanni A.M.; Dowson, Sophie E.; Demandt, Laura; Walter, Gina; Canavan, James B.; Scotta, Cristiano; Menon, Bina; Chana, Prabhjoat S.; Khamri, Wafa; et al.
<x xml:space="preserve">Abstract</x> Treg cells are critical for the prevention of autoimmune diseases and are thus prime candidates for cell‐based clinical therapy. However, human Treg cells are "plastic", and are able to produce IL‐17 under inflammatory conditions. Here, we identify and characterize the human Treg subpopulation that can be induced to produce IL‐17 and identify its mechanisms. We confirm that a subpopulation of human Treg cells produces IL‐17 in vitro when activated in the presence of IL‐1β, but not IL‐6. "IL‐17 potential" is restricted to population III (CD4+CD25hiCD127loCD45RA−) Treg cells expressing the natural killer cell marker CD161. We show that these cells are functionally as suppressive and have similar phenotypic/molecular characteristics to other subpopulations of Treg cells and retain their suppressive function following IL‐17 induction. Importantly, we find that IL‐17 production is STAT3 dependent, with Treg cells from patients with STAT3 mutations unable to make IL‐17. Finally, we show that CD161+ population III Treg cells accumulate in inflamed joints of patients with inflammatory arthritis and are the predominant IL‐17‐producing Treg‐cell population at these sites. As IL‐17 production from this Treg‐cell subpopulation is not accompanied by a loss of regulatory function, in the context of cell therapy, exclusion of these cells from the cell product may not be necessary.